Satellite Telemetry and Image Reception with Software Defined Radio Applied to Space Outreach Projects in Brazil - PERALTA,DAVID JULIAN M. (2018)
Abstract Software Defined Radio (SDR) uses a processor, a special receiver and software that play the main parts of the receiver (mixer, filters, amplifiers, modulators, demodulators, etc.) and it is quite advantageous for its flexibility and compact size as it reduces the amount of hardware components while adapting for different needs. This work briefly presents the SDR concept and approach for obtaining satellite telemetries and imagery in the context of different modulation schemes, link budget requirements and different satellites types. Two case studies are presented for supporting affordable ground segment and promoting satellites projects in Brazil. Reception from the 1st Brazilian picosatellite, Tancredo-1, with specific software developed, UbaTM is presented for obtaining satellite raw telemetries, convert them to engineering value and friendly present on user screen. A series of support software packages are then introduced so that one can pipeline various operations and automate tasks in the ground station. Finally, a second study case was performed in order to receive NOAA class satellites imagery over VHF band and decoded by specific software freely available. Using the proposed SDR approach, it can adapt to projects mainly those with a limited budget and outreach for major inclusion on space topics in Brazil.